2019
DOI: 10.1093/nar/gkz751
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the RNA cap epitranscriptome reveals novel caps in cellular and viral RNA

Abstract: Chemical modification of transcripts with 5′ caps occurs in all organisms. Here, we report a systems-level mass spectrometry-based technique, CapQuant, for quantitative analysis of an organism's cap epitranscriptome. The method was piloted with 21 canonical caps—m7GpppN, m7GpppNm, GpppN, GpppNm, and m2,2,7GpppG—and 5 ‘metabolite’ caps—NAD, FAD, UDP-Glc, UDP-GlcNAc, and dpCoA. Applying CapQuant to RNA from purified dengue virus, Escherichia coli, yeast, mouse tissues, and human cells, we discovered new cap stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
155
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(178 citation statements)
references
References 79 publications
7
155
0
3
Order By: Relevance
“…Recently an alternative LC-MS method for detecting mRNA caps was reported [53]. In addition to dinucleotide caps, a variety of rare non-canonical metabolite mRNA caps were detected in mammalian cells including NAD-caps, which have only recently been described in mammalian cells and FAD-caps, UDP-Gluc-caps and UDP-GlucNAc-caps which were not previously known to exist in mammals [54].…”
Section: Discussionmentioning
confidence: 99%
“…Recently an alternative LC-MS method for detecting mRNA caps was reported [53]. In addition to dinucleotide caps, a variety of rare non-canonical metabolite mRNA caps were detected in mammalian cells including NAD-caps, which have only recently been described in mammalian cells and FAD-caps, UDP-Gluc-caps and UDP-GlucNAc-caps which were not previously known to exist in mammals [54].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of A to m 6 A vary between studied cell lines, but usually is more than 50% (47). Numerous studies revealed that the 5’ cap composition is dependent on the organism, tissue or cell type (5,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The 5’ cap structures and cap proximal RNA sequences have been initially investigated by radioactivity-based chemo-enzymatic methods (1,2,4,9), but more recently, transcriptome-wide MS-based techniques enabled more robust and quantitative analyses leading to interesting discoveries (5). 2’- O Methylation is the most common modification of the first transcribed nucleotide in human cells and other vertebrates (1,2,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Processing of the 5′ and 3′ ends of mRNA has long been studied. 7,8 In contrast, our understanding of writing epitranscriptomic modifications and alternative mRNA splicing are rapidly advancing as a result of next-generation sequencing (NGS) and expansion of bioinformatic tools. [1][2][3][4] The best studied epitranscriptomic modification in mRNA is N 6 -methyladenosine (m 6 A; Figure 1A), in which deposition of the methyl group on A nucleotides occurs in specific sequence motifs; however, not all such sequences are modified.…”
mentioning
confidence: 99%